Efficacy of Eye Movement Desensitization Reprocessing (EMDR) in Improving Self-Regulation of In-House Filipino Clients with Substance-Use-Disorder - Andres V. Virrey Jr.; Jemerson Naceno Dominguez (Universitas Katolik Soegijapranata, 2021)
Abstract: Drug addiction is considered as a global epidemic which drastically affects millions of people worldwide, damaging an individual’s physiological, social, and psychological facets. One of the constructs that has been determined as an essential factor in the development of a variety of addictive behaviors is self-regulation. It plays an important role in predicting, maintaining, and treating addiction. In this study, the efficacy of Desensitization of Triggers and Urge Reprocessing (DeTUR), an Eye Movement Desensitization Reprocessing (EMDR) addiction protocol, in improving self-regulation was tested among fourteen (14) in-house clients of two drug treatment and rehabilitation centers using sequential explanatory mixed method research design wherein Self-regulation Inventory-Short Version (SRI-S) and individual interviews were employed. Results explicitly proved that self-regulation scores obtained significantly differed before, after, and even the delivery of delayed posttest using the EMDR as an intervention. The study confirmed that EMDR enhances the clients’ self-regulations (Overall SRI) and the sub-areas: positive actions, controllability, expressions of feelings and needs, assertiveness, and well-being seeking. Themes generated using thematic analysis further established a basis for the efficacy of EMDR.Keywords: drug addiction, self-regulation, Eye-movement Desensitization Reprocessing (EMDR), Desensitization of Triggers and Urge Reprocessing (DeTUR)